Migration and intention to return: entrepreneurial intentions of the diaspora in post-conflict economies. Issue 4 (4th July 2019) - Krasniqi, Besnik A.; Williams, Nick
ABSTRACT: This article examines the intentions of the diaspora to return to their homeland and engage in entrepreneurial activity. We focus on post-conflict economies where the development potential of return migration is significant. Our article demonstrates that the entrepreneurial intentions of returning diaspora are affected by their level of trust and perceptions of risk in institutions at home. Through a survey of diaspora returning to Kosovo, the paper finds that business experience has a negative relationship on probability to return, but it has a positive relationship on entrepreneurial intentions. However, those with professional and qualified jobs are more likely to have intentions to return, but less likely to have entrepreneurial intentions. The paper contributes to academic research on the central importance of institutions to post-conflict development, demonstrating that by enhancing the institutional environment investment can be attracted home.